Persepsi Peserta Didik terhadap Pengelolaan Kegiatan Ekstrakurikuler Pramuka di SMP Negeri se-Kecamatan Guguak Panjang Kota Bukittinggi - Imelda Imelda; Nelfia Adi; Nellitawati Nellitawati; Yulianto Santoso (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
This descriptive quantitative research investigated students' perceptions of the management of Scout extracurricular activities at public junior high schools in Guguak Panjang District, Bukittinggi City. The study was conducted in response to indications that several management functions, including planning, organizing, implementation, and evaluation, had not yet been fully optimized. The objective was to describe students' perceptions of Scout extracurricular management based on these four management dimensions. The study involved 102 respondents selected from a population of 2,684 seventh- and eighth-grade students using proportional random sampling. Data were collected through a five-point Likert questionnaire that had satisfied validity and reliability requirements. Descriptive statistical analysis using the mean score was employed to interpret the data. The findings revealed that students perceived the management of Scout extracurricular activities as good. The mean scores for planning, organizing, implementation, and evaluation were 4.02, 4.13, 4.07, and 4.18, respectively, with an overall mean of 4.12. These findings indicate that the management of Scout extracurricular activities has generally been implemented effectively. Nevertheless, improvements are still required in the planning aspect, particularly in scheduling activities that better accommodate students' academic responsibilities and participation.